Stakeholder influence capacity and the variability of financial returns to corporate social responsibility - Barnett, M (2007)
I argue that research on the business case for corporate social responsibility must account for the path-dependent nature of firm-stakeholder relations, and I develop the construct of stakeholder influence capacity to fill this void. This construct helps explain why the effects of corporate social responsibility on corporate financial performance vary across firms and time. I develop a set of propositions to aid future research on the contingencies that produce variable financial returns to investment in corporate social responsibility.